2015
DOI: 10.1017/s0007114515003621
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of sodium butyrate protects mice from the development of non-alcoholic steatohepatitis (NASH)

Abstract: Overnutrition, insulin resistance and an impaired intestinal barrier function are discussed as critical factors in the development of nonalcoholic fatty liver disease. Not only butyrate-producing probiotics as well as supplementation of sodium butyrate (SoB) have been suggested to bear protective effects on liver damage of various aetiologies. However, whether an oral consumption of SoB has a protective effect on Western-style diet (WSD)-induced non-alcoholic steatohepatitis (NASH) and if so molecular mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
110
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(128 citation statements)
references
References 40 publications
14
110
1
Order By: Relevance
“…The gut microbiota metabolite butyrate, which obviously increased after FMT intervention, is a pivotal immune regulator and anti-inflammatory substance. It improves the hepatic insulin resistance and attenuates HFD-induced steatohepatitis 23, 3941 . In this study, the pro-inflammatory factors in the liver, such as TNF-α, MCP-1, IL-1 and IL-6, were decreased in the FMT-treated mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gut microbiota metabolite butyrate, which obviously increased after FMT intervention, is a pivotal immune regulator and anti-inflammatory substance. It improves the hepatic insulin resistance and attenuates HFD-induced steatohepatitis 23, 3941 . In this study, the pro-inflammatory factors in the liver, such as TNF-α, MCP-1, IL-1 and IL-6, were decreased in the FMT-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement in hepatic steatosis may result from enhanced intrahepatic insulin sensitivity after FMT. Others showed that in mice with NASH, supplementation of sodium butyrate caused increased expression of insulin receptor in the liver, leading to improved liver insulin sensitivity and hepatic steatosis 41 . Here we also showed that in mice subjected to FMT, the protein level of insulin receptor was upregulated, following a significant increase of butyrate concentration in cecal content after FMT.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that supplementation of butyrate producing probiotics improved the lipid profile and reduced the progression of obesity in mice [26]. Further, intervention of NaB reduced the development of non-alcoholic steatohepatitis (NASH) in C57BL/6J mice [37]. Tributyrin (a pro-drug of butyrate) also attenuates the obesity-associated inflammation and insulin-resistance in HFD fed mice [23].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, simply adding butyrate to the diets of mice with steatosis reduced liver injury 70 . A meta-analysis found that this probiotic use can reduce serum levels of ALT and aspartate aminotransferase (AST), inflammation, and insulin resistance in NAFLD patients 71 .…”
Section: Manipulating the Microbiomementioning
confidence: 99%